2018
DOI: 10.1016/j.bjan.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Escore CR‐POSSUM e Índice de Apgar Cirúrgico como fatores preditivos para a alocação de pacientes após cirurgia colorretal

Abstract: Both CR-POSSUM and SAS were associated with the clinical decision to admit a patient to the high-dependency units/intensive care units immediately after surgery. CR-POSSUM alone showed a better discriminative capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In 1996, Whiteley et al 5 found that POSSUM overestimated the postoperative mortality rate, and they revised the statistical regression equation, which was referred to as P-POSSUM. Thus far, POSSUM and P-POSSUM have been studied in colorectal and orthopedic fields, 6 , 7 but no research has been reported in elderly patients undergoing hepatobiliary and pancreatic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In 1996, Whiteley et al 5 found that POSSUM overestimated the postoperative mortality rate, and they revised the statistical regression equation, which was referred to as P-POSSUM. Thus far, POSSUM and P-POSSUM have been studied in colorectal and orthopedic fields, 6 , 7 but no research has been reported in elderly patients undergoing hepatobiliary and pancreatic surgery.…”
Section: Introductionmentioning
confidence: 99%